ChemInform Abstract: Preparation and Crystal Structure of a New Lithium Vanadium Fluoride Li2VF6 with Trirutile‐Type Structure. Issue 21 (2nd May 2013) - Nakhal, Suliman; Weber, Dominik; Lerch, Martin
Abstract The new title compound is obtained together with Li3VF6 from a 2:1 mixture of LiF and VF4 (monel capsule, 500 °C, 12 h).